Operational management and strategic scenarios of implementing artificial intelligence in entrepreneurship infrastructure organizations - Dmytro Antoniuk (Менеджмент та підприємництво: тренди розвитку, 2025)
The article examines the role of operational management in implementing various scenarios of artificial intelligence (AI) strategy adoption within entrepreneurship infrastructure organizations, such as chambers of commerce and industry, consulting firms, incubators, and government business support institutions. The study proposes a conceptual model that considers two key drivers: organizational readiness and the level of competitive pressure. The research methodology employs a matrix approach that identifies four AI implementation strategy scenarios.